Two modes of relating to nature in contemporary Japanese architecture - Stevanovic, Vladimir (Arhitektura i urbanizam, 2013)
Abstract The text questions the relationship between architecture and nature in the context of Japanese culture. The close connection with nature is noticeable incorporated into contemporary architectural approaches undertaken by Japanese authors such as Tadao Ando and Kengo Kuma. In some works by these architects it is possible to follow not only the manifestation of architecture in nature, but also the way in which nature is expressed in architecture. However, Ando’s and Kuma’s architecture, as the subject of analysis, will not be discussed in terms of a quasi-ethical and socially-engaged understanding of the importance of ecologically oriented approach in dealing with the environment, nor as a high-tech options developed within the paradigm of green design trend. The intention is through projects by the aforementioned architects recognize and examine the cultural and philosophical dimension, which is undoubtedly related to their naturally-oriented architecture. Interpretation of the relation to nature of the Japanese tradition raises questions of a specific connection of nature and beauty that is the framework of this culture. The aim of the text is to establish a theoretical focus that would enable a wider and clearer view of certain contemporary tendencies in Japanese architectural practice.